Remote Health Monitoring System for Quarantined/Isolated Cases - Aloqalaa, Ziyad (British Journal of Healthcare and Medical Research, 2023)
Global viruses could affect many people’s health and quality of life, as seen during the Coronavirus (COVID-19) pandemic. Most people infected with COVID-19 have experienced mild to moderate respiratory illness and recover without special treatment. However, some cases have developed into serious illnesses, especially cases with previous conditions like cardiovascular disease, diabetes, chronic respiratory disease, and cancer. Social distancing, quarantine, and isolation are the most effective ways to prevent viruses such as COVID-19 from spreading. Consequently, this social distancing creates challenges to monitor vital signs of quarantined and isolated cases. Hence, a medical practitioner needs a system that facilitates the monitoring process. This research will develop a remote health monitoring system that helps monitor vital signs of quarantined and isolated cases. This system has many benefits, including minimizing direct contact between healthcare providers and quarantined/isolated cases, predicting the number of cases that might need critical care treatment in the future, and facilitating the development of a national health registry regarding any pandemic. A remote health monitoring system is a sensor-based system to measure body temperature, respiratory rate, oxygen saturation (SpO2), and heart rate. This system will be interactive by incorporating an Internet of Things (IoT) feature that monitors cases in real-time or at specified intervals, then sends the result to healthcare providers.